Information society: the analysis of modern concepts of social management (Журналистика сериясы, 2016)
The article analyzes the exerted influence on modern society informatization process, indicated the high role of information exposed to contemporary social structures change. Clarifies their basic meanings in the science of man. With cultural and social and economic points of view, the term «global information society» due to the continuous increase in the growth of information involve the concept of «information industry». At the present stage of information certainly are a valuable resource. However, do not go unheeded, and the flow of information, which can be an obstacle to human values. The purpose of information is understood as a global rationalization of intellectual activity. The involvement of citizens in the process of informatization for the state is not dangerous, on the contrary, if the information is available to them in a timely and complete, then it would be beneficial for the state and for the people.